Interaction Between Type I and II Coagents and Polybutadiene Isomers on Crosslinking Systems Using Organic Peroxide. Issue 1 (21st December 2022) - Neumann, Chaiane; Romanzini, Daiane; Andrade, Mara Z.; Francisquetti, Edson L.
Abstract: This study aims to evaluate the influence of types I and II coagents on different polybutadiene isomers vulcanized with organic peroxides. In this study, dicumyl peroxide (DCP) is used in association with coagents ethylene glycol dimethacrylate (EGDMA) and triallyl isocianurate (TAIC) in the crosslinking of high cis‐1, 4‐polybutadiene and high vinyl‐1, 2‐polybutadiene isomers. The results reveal that using a type I coagent, EGDMA increases the crosslink density as the amount of coagent is increased. The curing index of the samples is positively influenced by coagent type I, mainly when vinyl‐1, 2‐polybutadiene is used.